FATTY ACIDS COMPOSITION OF BAMBARA GROUNDNUT (VIGNA SUBTERRANEAN (L) VERD C) GROWN IN MADOBI, KANO STATE-NIGERIA - A. J. Alhassanm; M. S. Sule; H. Abubakar; T. M. Abdulmumin; M. A. Dangambo (European Scientific Journal, ESJ, 2014)
Introduction: The important of research to evaluate the fatty acids content of a neglected crop with nutritional potential cannot be over emphasis. Aim:this research work aimed at evaluating the fatty acid(s) profile of Bambara ground nut grown in Rimingado LGA. Methodology:The fatty acid content of a representative sample of the composite sample collected from Rimingado LGA of Kano- Nigeria was evaluated using GC – MS.Result:The oil was found to contain both saturated and unsaturated fatty acids that differ in chain length, number and positions of double bond (s).Thirty three (33) different fatty acids were detected including arachidic acid (eicosanoic acid).Detection vitamin C fatty acid conjugate (1-(+)-ascorbic acid 2, 6 dihexadecanoate)indicates the presence of vitamin C in the plant. The presence of arachidic acid (eicosanoic acid) implies that Bambara groundnut oil may be rich in essential fatty acid. The presence of unsaturated fatty acid indicates that Bambara groundnut oil could play a significant role in cardiovascular fitness; while that of saturated fatty acids implies that the oil could be a source of energy from non-carbohydrate. Conclusion:It is concluded that Bambara groundnut oil could play an important role in food and pharmaceutical industries.